OUTSOURCING DALAM PERSPEKTIF KARYAWAN: Studi Empiris Karyawan Outsourcing PT. Spirit Krida - Nasif, Khifni; Ni'mah, Istianah (Prodi Ekonomi Syariah Pascasarjana IAIN Kudus, 2016)
Outsourcing is one of the measures the efficiency of a company. Outsoursing also considered as an alternative to get a job so hopefully someone can meet their basic needs with the needs of dharuriyat, hajiyat, and tahsiniyat. Outsourcing can not be separated from social issues that always comes up, it was evident with the rise of workers' demonstrations for the system to work is removed because it is considered as a modern form of slavery. This study is a qualitative study with a phenomenological approach. Data were collected through interviews, observation and documentation. Then the data were analyzed by two analysis model, namely descriptive analysis within the framework of Islamic framework. The results showed that the dimensions of well-being in PT Spirit Activities of Indonesia in the employee's perspective, berdasarkant Maslahat concept includes, first, dharuriyat is appropriate salary Living Needs (KHL). Second, Hajiyyat such as training or education, health insurance (BPJS), work permits due to illness, and administrative assistance applying for a loan. Third, luxuries such as death benefits and cash rope of love, work clothes, musolla & cafeteria, incentives and leave huge day. Among the three dimensions of the well-being based on the concept of the necessities most dominant form of salary.